Pemodelan Luas Genangan Banjir Batang Lunto di Wilayah Kota Sawahlunto - Indra, Bambang Adi; Daud, Darwizal; Andriani, Andriani; Azra, Dio Syahlung (Jurnal Talenta Sipil, 2025)
Batang Lunto originates in Barangin District, Sawahlunto City, West Sumatra Province and flows eastwards, dividing Sawahlunto City in Lembah Segar District and empties into Batang Ombilin. The Batang Lunto River is included in the Ombilin Coal Mining Heritage Area of Sawahlunto and has been designated as a world cultural heritage by the United Nations Educational, Scientific and Cultural Organization (UNESCO). During the rainy season along the Batang Lunto river, flooding often occurs, while along the Batang Lunto river there are heritage and geopark assets which are tourism destinations in Sawahlunto City. This research aims to model the area of the Batang Lunto flood inundation in the Sawahlunto City area as a first step in mitigating the risk of flood disasters with an area under review of 125.70 Ha. Modeling was carried out using a hydrological and hydrodynamic approach using rainfall data, topography and river flow characteristics. This research utilizes simulation software to map flood-affected areas with various flow discharge scenarios. Flood inundation simulations were carried out using ArcGIS 10.3, HEC-Ras 6.3.1 software at return periods of 2, 5, 10, 25, 50, 100 years. The results of this research show that the flood inundation area resulting from the HEC RAS simulation at the 2-year return period with a discharge of 102.61 m3/s is 18.12 Ha or around 14.42% of the total area of the survey area in this study and respectively for return periods 5, 10, 25, 50, 100 annual is 20.43 Ha (16.25%), 38.38 Ha (30.53%), 45.84 Ha (36.48%), 55.56 Ha (44.20%), 63.70 Ha (50.68%).